Differences in Administrative Claims Data for Coronary Artery Bypass Grafting Between International Classification of Diseases, Ninth Revision and Tenth Revision Coding - Schaffer, Justin M. (JAMA Cardiol, 2021)
This cross-sectional study examines the changes in coding of coronary artery bypass graft procedures after the transition from the International Classification of Diseases, Ninth Revision to the Tenth Revision.